Response to Mindfulness-Based Cognitive Therapy Differs Between Chronic and Episodic Migraine. Issue 3 (June 2021) - Seng, Elizabeth K.; Conway, Alexandra B.; Grinberg, Amy S.; Patel, Zarine S.; Marzouk, Maya; Rosenberg, Lauren; Metts, Christopher; Day, Melissa A.; Minen, Mia T.; Buse, Dawn C.; Lipton, Richard B.
Abstract : Objective: Evaluate whether the benefits of Mindfulness-Based Cognitive Therapy for Migraine (MBCT-M) on headache disability differs among people with episodic and chronic migraine (CM). Methods: This is a planned secondary analysis of a randomized clinical trial. After a 30-day baseline, participants were stratified by episodic (6–14 d/mo) and CM (15–30 d/mo) and randomized to 8 weekly individual sessions of MBCT-M or wait list/treatment as usual (WL/TAU). Primary outcomes (Headache Disability Inventory; Severe Migraine Disability Assessment Scale [scores ≥ 21]) were assessed at months 0, 1, 2, and 4. Mixed models for repeated measures tested moderation with fixed effects of treatment, time, CM, and all interactions. Planned subgroup analyses evaluated treatment*time in episodic and CM. Results: Of 60 participants (MBCT-M N = 31, WL/TAU N = 29), 52% had CM. CM moderated the effect of MBCT-M on Severe Migraine Disability Assessment Scale, F (3, 205) = 3.68, p = 0.013; MBCT-M vs WL/TAU reduced the proportion of people reporting severe disability to a greater extent among people with episodic migraine (−40.0% vs −14.3%) than CM (−16.4% vs +8.7%). Subgroup analysis revealed MBCT-M (vs WL/TAU) significantly reduced Headache Disability Inventory for episodic ( p = 0.011) but not CM ( p = 0.268). Conclusions: MBCT-M is a promising treatment for reducing headache-related disability, with greater benefits in episodic than CM. Trial Registration Information: ClinicalTrials.gov Identifier: NCT02443519. Classification of Evidence: This study provides Class III evidence that MBCT-M reduces headache disability to a greater extent in people with episodic than CM.